Experimental studies of shell and tube heat exchanger with cylindrical flow turbulators - N. Yu. Nikulin; Yu. V. Elistratova (Vestnik MGSU)
Introduction. Heat exchangers are important equipment in modern heat supply. This equipment is very common. Modernization of shell-and-tube heat exchangers is an important direction. The purpose of modernization is to increase the heat transfer coefficient. A heat exchanger which tubes are equipped with plates was developed. Cylindrical turbulators (ribs) are located on the plates. The experiment is important for the development of a new heat exchanger. The experimental conditions correspond to the real heat supply system.Materials and methods. The full-scale stand was used for the experiment. The stand represents an independent heating system of the building. The planning of the experiment is based on the temperature schedule of the boiler house and the temperature schedule for the consumer. Mathematical processing of the results was carried out.Results. For a heat exchanger (with turbulators), the values of the heat transfer coefficient were obtained at different outdoor temperatures during the heating period. The dependences of the heat transfer coefficient on the temperature difference are obtained. This was done at coolant velocities in the annular space of 0.16 and 0.32 m/s. Discrepancies are adequate, statistically significantly describe the results of the experiment. The heat transfer coefficient of the heat exchanger (with turbulators) turned out to be greater than that of the serial one. This parameter is 22 % more at a speed of 0.16 m/s, 23 % more at a speed of 0.32 m/s on average for the heating period.Conclusions. The heat transfer coefficient increased for the heat exchanger with turbulators by an average of 23 %. The turbulence of the coolant affects this increase. The dimensions will be much smaller for such a heat exchanger than for an apparatus with smooth tubes. Tube with cylindrical turbulators is recommended for use in different equipment. This can be used in shell-and-tube heat exchangers, air heaters, heaters, economizers.